Pengaruh Hand Therapy Exercise Terhadap Motorik Halus Anak Usia 5-6 Tahun di TK PKK Puji Rahayu Kabupaten Tuban - Risma Mega Mustika Dwi Milenia (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2022)
Preschoolers are those aged 4-6 years, usually, they follow the kindergarten program. Children of this age experience very rapid development from the fine motor and gross motor development, to language, cognitive and emotional development. Children who do not get good stimulation will experience developmental delays, one of which is fine motor skills. The purpose of this study was to determine the effect of hand therapy exercises on the fine motor skills of children aged 5-6 years at PKK Puji Rahayu Kindergarten, Tuban Regency.The design of this research is quasi-experimental using a pretest-posttest control group design approach. Samples were taken from the population that met the inclusion criteria and exclusion criteria at PKK Puji Rahayu Kindergarten, Tuban Regency in August 2022 as many as 20 respondents with purposive sampling. The independent variable is hand therapy exercise while the dependent variable is a fine motor. An instrument using Bender Gestalt Test.The results showed the effect of hand therapy exercise on the fine motor skills of children aged 5-6 years with the Paired Simple T-Test version 25, the results obtained in the control group p-value of 0.443 (p-value 0.05) while in the experimental group had p-value value 0.001 (p-value 0.05).It can be concluded that in the experimental group there is an effect of hand therapy exercise on the fine motor skills of children. It is hoped that kindergarten teachers can apply hand therapy exercises as stimulation to improve fine motor development, especially in children aged 5-6 years.